Alcohol drinking patterns and liver cirrhosis risk: analysis of the prospective UK Million Women Study. (January 2019) - Simpson, Rachel F; Hermon, Carol; Liu, Bette; Green, Jane; Reeves, Gillian K; Beral, Valerie; Floud, Sarah; ,
Summary: Background: Alcohol is a known cause of cirrhosis, but it is unclear if the associated risk varies by whether alcohol is drunk with meals, or by the frequency or type of alcohol consumed. Here we aim to investigate the associations between alcohol consumption with meals, daily frequency of consumption, and liver cirrhosis. Methods: The Million Women Study is a prospective study that includes one in every four UK women born between 1935 and 1950, recruited between 1996 and 2001. In 2001 (IQR 2000–03), the participants reported their alcohol intake, whether consumption was usually with meals, and number of days per week it was consumed. Cox regression analysis yielded adjusted relative risks (RRs) for incident cirrhosis, identified by follow-up through electronic linkage to routinely collected national hospital admission, and death databases. Findings: During a mean of 15 years (SD 3) of follow-up of 401 806 women with a mean age of 60 years (SD 5), without previous cirrhosis or hepatitis, and who reported drinking at least one alcoholic drink per week, 1560 had a hospital admission with cirrhosis (n=1518) or died from the disease (n=42). Cirrhosis incidence increased with amount of alcohol consumed (≥15 drinks [mean 220 g of alcohol] vs one to two drinks [mean 30 g of alcohol] per week; RR 3·43, 95% CI 2·87–4·10; p<0·0001). About half of the participants (203 564 of 401 806) reported usually drinking with meals and, after adjusting for amount consumed, cirrhosis incidence was lower for usually drinking with meals than not (RR 0·69, 0·62–0·77; p<0·0001; wine-only drinkers RR 0·69, 0·56–0·85; all other drinkers RR 0·72, 0·63–0·82). Among 175 618 women who consumed seven or more drinks per week, cirrhosis incidence was greater for daily consumption than non-daily consumption (adjusted RR 1·61, 1·40–1·85; p<0·0001). Daily consumption, together with not drinking with meals, was associated with more than a doubling of cirrhosis incidence (adjusted RR 2·47, 1·96–3·11; p<0·0001). Interpretation: In middle-aged women, cirrhosis incidence increases with total alcohol intake, even at moderate levels of consumption. For a given weekly intake of alcohol, this excess incidence of cirrhosis is higher if consumption is usually without meals, or with daily drinking. Funding: UK Medical Research Council and Cancer Research UK.